2015
DOI: 10.1681/asn.2014050470
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of WNK4 on the Na+–Cl− Cotransporter Is Modulated by Intracellular Chloride

Abstract: It is widely recognized that the phenotype of familial hyperkalemic hypertension is mainly a consequence of increased activity of the renal Na + -Cl 2 cotransporter (NCC) because of altered regulation by with no-lysine-kinase 1 (WNK1) or WNK4. either by low chloride hypotonic stress or coinjection of oocytes with the solute carrier family 26 (anion exchanger)-member 9 (SLC26A9) cRNA, promoted WNK4 autophosphorylation and increased NCC-dependent Na + transport in a WNK4-dependent manner. Substitution of the leu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 141 publications
(154 citation statements)
references
References 31 publications
(45 reference statements)
7
144
0
3
Order By: Relevance
“…The crystal structure of WNK1 kinase domain indicates that residues K233 and D368 are in close vicinity perhaps generating ionic interactions critical for the kinase domain to exerts its effect upon target proteins (21). Recently, Bazúa-Valenti et al (4) demonstrated that introduction of the double mutant KDDK in WNK4 lacking the Cl Ϫ -binding sites prevented the activation of NCC and eliminated most of its activity. Thus we generated the double-charge K233D/D368K mutant (KDDK) into L-WNK1-⌬11 to analyze the kinase dependency on the activity of KCC3a after cell swelling.…”
Section: Inhibitory Effect Of L-wnk1-⌬11 On the Renal Kmentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structure of WNK1 kinase domain indicates that residues K233 and D368 are in close vicinity perhaps generating ionic interactions critical for the kinase domain to exerts its effect upon target proteins (21). Recently, Bazúa-Valenti et al (4) demonstrated that introduction of the double mutant KDDK in WNK4 lacking the Cl Ϫ -binding sites prevented the activation of NCC and eliminated most of its activity. Thus we generated the double-charge K233D/D368K mutant (KDDK) into L-WNK1-⌬11 to analyze the kinase dependency on the activity of KCC3a after cell swelling.…”
Section: Inhibitory Effect Of L-wnk1-⌬11 On the Renal Kmentioning
confidence: 99%
“…The responsiveness of the SLC12 family members to changes in extracellular chloride parallels their phosphorylation state, suggesting that these transporters are controlled by chloride-sensitive protein kinases (4,43,64). In a recent study, Piala et al (46) demonstrated that chloride stabilizes the inactive conformation of L-WNK1, preventing kinase autophosphorylation and activation.…”
Section: Effect Of the Elimination Of The Chloride Binding Site On L-mentioning
confidence: 99%
“…En effet, en fonction des modèles utilisés, WNK4 et WNK1 présentaient, dans certaines études, un rôle activateur de NCC et, dans d'autres, un rôle inhibiteur (voir plus loin). Deux publications récentes de notre équipe ont permis de commencer à expliquer ces contradictions [7,8]. La première démontre que les résultats contradictoires des études portant sur la régulation de NCC par WNK1 provenaient de l'utilisation d'un ADN complémen-taire (ADNc) de WNK1 présentant une mutation inactivatrice [8].…”
Section: Wnk1-wnk4 Et Hypertension Hyperkaliémique Familialeunclassified
“…La première démontre que les résultats contradictoires des études portant sur la régulation de NCC par WNK1 provenaient de l'utilisation d'un ADN complémen-taire (ADNc) de WNK1 présentant une mutation inactivatrice [8]. La deuxième montre que les effets activateurs et inhibiteurs de WNK4 sur la régulation de NCC sont en fait présents au sein d'une même cellule et qu'ils sont modulés par la concentration intracellulaire de chlorure [7]. Dans cette revue, nous reviendrons sur ces récentes découvertes et nous proposerons un nouveau modèle pour expliquer le rôle que jouent WNK1 et WNK4 dans la régulation du transport de NaCl et de potassium dans le rein.…”
Section: Wnk1-wnk4 Et Hypertension Hyperkaliémique Familialeunclassified
See 1 more Smart Citation